Value of pharmaceuticals: Improving product demand through innovative research and development in Palestinian and Jordanian firms - Alrub, Rafat Abu (Edelweiss Applied Science and Technology, 2024)
This study investigates the sustainability of the pharmaceutical business in Palestine and Jordan by examining the impact of R&D intensity on company performance. The study sample consisted of pharmaceutical companies listed on the Amman and Palestine Stock Exchanges, where the descriptive analytical approach was used to achieve the study's objectives, which numbered (6) companies for ten years from 2013 to 2022. The study's dependent variable, "Performance and value of the company’s Return on Assets (ROA), Earnings Per Share (EPS), and Tobin's Q, and the independent variables were R&D intensity (RDI) and selling and marketing expenses (SMI). A statistical analysis package (STATA) was used to achieve the study's objectives and test its hypotheses. The study analyzed the impact of variables (RDI, SMI,) on the performance and value of pharmaceutical companies. Variables (RDI, SMI, FS, CP, and LEV) had no significant influence on these factors. However, the MS has a significant impact on these factors. The study also found that while variables (SMI and FS) had a significant effect on pharmaceutical companies' performance and value, the variables (RDI, MS, CP, and LEV) had no significant influence on either. This study offers significant implications for the sustainability of pharmaceutical companies, investors, and academic research centers. Governments, including health ministries, should reevaluate R&D spending to bring about a qualitative change that will allow these businesses to innovate and sustainably contribute to the preservation of healthcare.